PENGARUH MEDIA PEMBELAJARAN BERBASIS GAME EDUKASI WORDWALL TERHADAP HASIL BELAJAR SISWA KELAS IX DI UPT SPF SMP NEGERI 21 MAKASSAR - Fuad Fauzan; Nurindah; Sadriana Ayu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Wordwall learning media impact research on learning class ix in upt SPF 21st country junior high school makassar. The study was intended to learn how to influence learning media based on the game the education on wordwall to students in upt SPF 21st country junior high school. The sample in this study is a class ix f upt SPF public junior high school of 28 people/respondents. The design of the research used in this study was one shot case design, where it was done to compare the conditions before and after being treated in the learning process. Studies have shown that the use of the mobile media game education on wordwall is affecting students' learning on Indonesian subjects, especially narrated text material.